2017
DOI: 10.1108/aaouj-09-2017-0030
|View full text |Cite
|
Sign up to set email alerts
|

The behavioural intention to use video lecture in an ODL institution

Abstract: Purpose The purpose of this paper is to gain insight into learners’ behavioural intention to use the video lectures as their learning material. The behavioural intention construct is measured in terms of perceived ease of use and perceived usefulness of video lectures. It is hoped that the findings of this study will provide feedback as to learners’ intention to use as well as guidelines on how to improve the development of video lectures as the university gears to offer more courses in the fully online mode i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(31 reference statements)
0
4
0
2
Order By: Relevance
“…Thus, PE affects BI directly while EE and SI affect BI indirectly. Other studies of e-learning implementation using interactive videos at Open University Malaysia (OUM) also showed positive results where there is positive perception of video lectures implementation in term of Ease of Use and Usefulness [7]. Ease p-ISSN : 2685-9106 e-ISSN : 2686-0384 ADI International Conference Series Adoption of Video Learning SOPs… 187 of Use and Usefulness are found in IDT and it is similar to EE on UTAUT model [16], [20].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, PE affects BI directly while EE and SI affect BI indirectly. Other studies of e-learning implementation using interactive videos at Open University Malaysia (OUM) also showed positive results where there is positive perception of video lectures implementation in term of Ease of Use and Usefulness [7]. Ease p-ISSN : 2685-9106 e-ISSN : 2686-0384 ADI International Conference Series Adoption of Video Learning SOPs… 187 of Use and Usefulness are found in IDT and it is similar to EE on UTAUT model [16], [20].…”
Section: Discussionmentioning
confidence: 81%
“…It measures the degree of easiness regarding the usage of technology and a positive predictor for technology acceptance [20]. EE which also identical to perceived ease of use (PEOU) also predicted to influence BI because PEOU significantly impacting BI in the adoption of video learning [7] and adoption of flipped classroom [13]. Thus, this study provides below hypothesis.…”
Section: Ii6 Relationship Between Effort Expectancy (Ee) and Behavior...mentioning
confidence: 77%
See 1 more Smart Citation
“…video tutorial sangat penting digunakan dalam pengajaran dan pembelajaran karena banyak keuntungan yang diberikannya. Pengajaran dan proses pembelajaran dapat lebih ditingkatkan dan dengan video tutorial, siswa dapat belajar di mana saja kapan saja (Chiam, Woo, Chung, & K.P. Nair, 2017).…”
Section: Pendahuluanunclassified
“…A portfolio of learning strategies and materials that can cater to the various needs of learners across a range of learning environments needs to be created [7]. Several studies have also found challenges posed by online learning to students during MCO [8].…”
Section: Introductionmentioning
confidence: 99%